The Effect of Social Media Use and ICT Utilization on Student Learning Behavior and Learning Achievement - Indah Afidah Rahman; Masita (Institute of Information Technology and Social Science (IITSS), 2022)
This study examines the influence of the use of social media (USM) and information and communication technology (ICT) on learning behavior and student achievement. In today's digital era, social media and ICT have become an integral part of everyday life, including in the context of education. The use of social media and ICT has changed the way students interact and learn. Some experts argue that social media and ICT can support a more active, constructive and collaborative learning process. However, there are also concerns that excessive use can disrupt learning behavior and reduce students' academic performance. This study collected data from 207 students from several universities in Jambi Province through a Google Form-based questionnaire. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS- SEM) model to evaluate the relationship between the variables studied. The results showed that the use of social media and ICT has positive and negative impacts on students' learning behavior and learning achievement, depending on the way and intensity of use.